Tannic Acid with Antiviral and Antibacterial Activity as A Promising Component of Biomaterials—A Minireview - Kaczmarek, Beata (Materials, 2020)
As a phenolic acid, tannic acid can be classified into a polyphenolic group. It has been widely studied in the biomedical field of science because it presents unique antiviral as well as antibacterial properties. Tannic acid has been reported to present the activity against Influeneza A virus, Papilloma viruses, noroviruses, Herpes simplex virus type 1 and 2, and human immunodeficiency virus (HIV) as well as activity against both Gram-positive and Gram-negative bacteria as Staphylococcus aureus, Escherichia coli, Streptococcus pyogenes, Enterococcus faecalis, Pseudomonas aeruginosa, Yersinia enterocolitica, Listeria innocua. Nowadays, compounds of natural origin constitute fundaments of material science, and the trend is called “from nature to nature”. Although biopolymers have found a broad range of applications in biomedical sciences, they do not present anti-microbial activity, and their physicochemical properties are rather poor. Biopolymers, however, may be modified with organic and inorganic additives which enhance their properties. Tannic acid, like phenolic acid, is classified into a polyphenolic group and can be isolated from natural sources, e.g., a pure compound or a component of a plant extract. Numerous studies have been carried out over the application of tannic acid as an additive to biopolymer materials due to its unique properties. On the one hand, it shows antimicrobial and antiviral activity, while on the other hand, it reveals promising biological properties, i.e., enhances the cell proliferation, tissue regeneration and wound healing processes. Tannic acid is added to different biopolymers, collagen and polysaccharides as chitosan, agarose and starch. Its activity has been proven by the determination of physicochemical properties, as well as the performance of in vitro and in vivo studies. This systematics review is a summary of current studies on tannic acid properties. It presents tannic acid as an excellent natural compound which can be used to eliminate pathogenic factors as well as a revision of current studies on tannic acid composed with biopolymers and active properties of the resulting complexes.